Broiler Pigmentation Using Pigment Concentrate Extracted From Legumes Leaves - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Legume leaves contain high amount of caroEcnoids which potential for pigmentation. Previous experiment had developed a technology to extract the pigment from legume leaves ((.31irradia septum, Lericactur kTreockithala, Calliandrcr wiorhyrsus and Sesbania grond(tlorei. ,) and bound to a carrier. The purpose of this experiment is to prove that this product (pigment concentrate = PC) can be used as a piginentor for broiler skin. The experiment was carried out using 216 DOC strain 'Indian River" placed L11 Z7 wired cages which had S chicks in each. The design of experiment was Completely Randomized Design with 9 typos of diets containing 0.3 and 0.6% of PC from 4 types of legume leaves and ha sal diet (without PC) Parameters measured were body weight, feed consumption, feed conversion and shank colour. Analysis of carotenoids was also carried out on PC, feed and liver. The results showed that there were no significant difference (P > 0.05 ) among treatments on body weight gain( 823 -419K grams), feed consumption ( t 247 - 1442 grains) and feed conversion(1.46 -1.66). While the shank colour was significantly different (P < 0.05) among treatments The highest score was found using 0.6% PC from Calliandra icaves (8.67) 1-ollowcd by Sesbarua (8.50), Leucaena(7.53). and Gliricidia(7.25). The run nthopliv11 content in the liver was very low widi the highest value was that fed With diet containing PC from Calliandra leaves in conclusion. pigment concentrate extracted from Calliandia leaves was the best pigineutar and caused no negative effect to the performance. of birds.